Water Treatment Using Natural Coagulant and Electrocoagulation Process: A Comparison Study - Tofik Gali Aba Lulesa; Dejene Beyene; Million Ebba; Goshu Kenea (International Journal of Analytical Chemistry)
Water treatment is the primary consideration before utilizing water for different purposes. Surface water is highly vulnerable to pollution, either due to natural or anthropogenic processes. The main targets of this study were to investigate surface water treatment using Moringa Oleifera (MO), the electrocoagulation process (EC), and the Moringa Oleifera assisted electrocoagulation process (MOAEC). The Moringa Oleifera, EC process, and Moringa Oleifera-assisted EC process are effective mechanisms for the removal of COD (Chemical Oxygen Demand), BOD (Biological Oxygen Demand), TDS (Total Dissolved Solids), phosphate, TSS (Total Suspended Solids), and color from surface water. Different operating parameters such as pH (5–11), the dosage of coagulant (0.2–0.5 g), contact time or reaction time (20–50 minutes), current (0.2–0.5 A), and settling time (5–20 minutes) were considered. The maximum removal efficiency using Moringa Oleifera and the EC process was COD (85.48%), BOD (78.50%), TDS (84.5%), phosphate (95.70%), TSS (93.90%), color (94.50%), and COD (90.50%), BOD (87%), TDS (97.50%), phosphate (89.10%), TSS (95.80%), and color (96.15%), respectively. Similarly, with the application of MOAEC, 91.47%, 89.35%, 97.0%, 90.20%, 9.10%, and 95.70% of COD, BOD, TDS, phosphate, TSS, and color were removed, respectively. The EC process and MOAEC were more effective in the removal of COD, BOD, TDS, TSS, and color than using MO. More phosphate was removed using MO than the EC process and MOAEC. Additionally, the effects of different operating parameters were studied on the removal efficiency.